2018
DOI: 10.1016/j.cbpa.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold acclimation on active ion transport in cricket ionoregulatory tissues

Abstract: Cold-acclimated insects defend ion and water transport function during cold exposure. We hypothesized that this is achieved via enhanced active transport. The Malpighian tubules and rectum are likely targets for such transport modifications, and recent transcriptomic studies indicate shifts in Na-K ATPase (NKA) and V-ATPase expression in these tissues following cold acclimation. Here we quantify the effect of cold acclimation (one week at 12°C) on active transport in the ionoregulatory organs of adult Gryllus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…These results are also informative in that they show that the Malpighian tubules are more temperature sensitive than the rectum and exhibit a greater degree of adjustment to K + transport following cold acclimation both in terms of thermal sensitivity and in absolute K + transport rates. This supports the idea that reduced Malpighian tubule K + clearance is a central problem for D. melanogaster at low temperatures, as is the case for crickets (Des Marteaux et al, 2018), and that its preservation is thus beneficial to the development of chill tolerance. The effects of cold acclimation on ion transport are independent of V-type H + -ATPase and Na + /K + -ATPase activity…”
Section: Rectal K + Reabsorption Is Lower In Cold-acclimated Fliessupporting
confidence: 83%
See 3 more Smart Citations
“…These results are also informative in that they show that the Malpighian tubules are more temperature sensitive than the rectum and exhibit a greater degree of adjustment to K + transport following cold acclimation both in terms of thermal sensitivity and in absolute K + transport rates. This supports the idea that reduced Malpighian tubule K + clearance is a central problem for D. melanogaster at low temperatures, as is the case for crickets (Des Marteaux et al, 2018), and that its preservation is thus beneficial to the development of chill tolerance. The effects of cold acclimation on ion transport are independent of V-type H + -ATPase and Na + /K + -ATPase activity…”
Section: Rectal K + Reabsorption Is Lower In Cold-acclimated Fliessupporting
confidence: 83%
“…Thus chill tolerance in coldadapted and -acclimated flies appears to be at least partially improved by improved tubule K + secretion at low temperature. In addition, in contrast to the tubule fluid secretion in CA D. melanogaster, a recent study on CA crickets found reduced fluid secretion rates at lower temperatures, suggesting that a different mechanism exists in the cold acclimation of these two insects (Des Marteaux et al, 2018).…”
Section: Physiological Plasticity Of the Malpighian Tubules Improves mentioning
confidence: 82%
See 2 more Smart Citations
“…As the seasons change from autumn to winter, insects use environmental cues such as day length and gradual decrease in temperature to sense the onset of winter and trigger physiological changes (Teets & Denlinger, ). Gradual climatic transitions provide insects the opportunity to acclimate to cold conditions (Jakobs, Gariepy, & Sinclair, ; Sinclair, Coello Alvarado, & Ferguson, ; Teets & Denlinger, ), and indeed cold acclimation directly impacts osmotic regulation to preserve ion homeostasis at low temperature (e.g., Andersen et al, ; Des Marteaux et al, ; MacMillan, Yerushalmi, Jonusaite, Kelly, & Donini, ). In D. melanogaster male reproductive behaviors are negatively influenced by severe cold exposure (Singh & Prasad, ), but exposure to brief cold acclimation (i.e., rapid cold hardening) preserves male reproductive behavior and success (Shreve et al, ).…”
Section: Discussionmentioning
confidence: 99%